Point Mutations in Yeast CBF5 Can Abolish In Vivo Pseudouridylation of rRNA - Zebarjadian, Yeganeh (American Society for Microbiology, 1999)
In budding yeast (Saccharomyces cerevisiae), the majority of box H/ACA small nucleolar RNPs (snoRNPs) have been shown to direct site-specific pseudouridylation of rRNA. Among the known protein components of H/ACA snoRNPs, the essential nucleolar protein Cbf5p is the most likely pseudouridine (Ψ) synthase. Cbf5p has considerable sequence similarity to Escherichia coli TruBp, a known Ψ synthase, and shares the “KP” and “XLD” conserved sequence motifs found in the catalytic domains of three distinct families of known and putative Ψ synthases. To gain additional evidence on the role of Cbf5p in rRNA biosynthesis, we have used in vitro mutagenesis techniques to introduce various alanine substitutions into the putative Ψ synthase domain of Cbf5p. Yeast strains expressing these mutated cbf5 genes in a cbf5Δ null background are viable at 25°C but display pronounced cold- and heat-sensitive growth phenotypes. Most of the mutants contain reduced levels of Ψ in rRNA at extreme temperatures. Substitution of alanine for an aspartic acid residue in the conserved XLD motif of Cbf5p (mutant cbf5D95A) abolishes in vivo pseudouridylation of rRNA. Some of the mutants are temperature sensitive both for growth and for formation of Ψ in the rRNA. In most cases, the impaired growth phenotypes are not relieved by transcription of the rRNA from a polymerase II-driven promoter, indicating the absence of polymerase I-related transcriptional defects. There is little or no abnormal accumulation of pre-rRNAs in these mutants, although preferential inhibition of 18S rRNA synthesis is seen in mutant cbf5D95A, which lacks Ψ in rRNA. A subset of mutations in the Ψ synthase domain impairs association of the altered Cbf5p proteins with selected box H/ACA snoRNAs, suggesting that the functional catalytic domain is essential for that interaction. Our results provide additional evidence that Cbf5p is the Ψ synthase component of box H/ACA snoRNPs and suggest that the pseudouridylation of rRNA, although not absolutely required for cell survival, is essential for the formation of fully functional ribosomes.